Mental capacity legislation : principles and practice / edited by Rebecca Jacob, Michael Gunn, Anthony Holland. - Jacob, Rebecca; Gunn, M. J. (Michael J.); Holland, Tony, 1948- (Cambridge University Press, 2019)
Crucial to health and social care practice, the Mental Capacity Act (MCA) 2005 safeguards decision-making within a legal framework. This book provides theoretical, practical and up-to-date guidance on mental capacity legislation. It focuses on the theory underpinning the principles of the MCA 2005, including historical background, and the practical challenges in applying legal statute in varied clinical settings, from hospitals to social care in community settings. Recent case law is detailed and examples of ethical dilemmas and medico-legal challenges feature, along with guidance to navigate these in clinical practice. Applying mental capacity principles in end-of-life decision-making is an area of discussion, as well as the future of legislative changes in the field. To be read alongside the MCA 2005 Code of Practice, this guide will support mental health and social care professionals in clinical settings.